Suspects’ Uncooperativeness: Maxim violation in police interviews - Salma Dwi Yuniartika (Passage, 2022)
This qualitative study investigates maxim violations in police interviews. The data used is a transcription of three videotapes of the US police interviews with three suspects, from 2012 until 2018 which are obtained online through the website of Forensic Linguistic Data and Resources (https://www.forensicling.com/data-collections). It is found that the suspects violate three out of four maxims in cooperative principles formulated by Grice in 1975. The suspects violate the maxim of quality to mislead the police from getting the truth by giving false information. The suspects violated the maxim of quantity by giving excessive as well as little information to shift the particular topic being discussed. Lastly, the maxim of relation is violated by the suspects to avoid answering the topic brought by the police by changing the topic abruptly. The finding of this study shows that the suspects are being uncooperative to employ language strategies during the interviews which cause maxim violations in order to defend themselves and prove themselves that they are innocent.